Kemitraan Sektor Swasta Dalam Layanan Pemadam Kebakaran di Kota Pontianak - Taufiqurrahman, Taufiqurrahman; Wijaya, Holi Bina (Magister Pembangunan Wilayah dan Kota,Undip, 2013)
The fire services is one of public services that should be provided by Pontianak City Government, as one of the cities with high-risk of fire disaster. In order to provide it, Pontianak City Government assisted by private fire-fighters institutions. One of this institutions is BPA Siantan. In conducting its duties, BPA Siantan cooperate with various parties. Then,